Potential of abiotic stress resistance in plants induced by melatonin - Mohd Fauzi, Noor Akhmazillah; Mohamed, Elizah; Ahmad Soberi, Nurul Aini; Rosli, Nur Farah Aina (Penerbit UTHM, 2022)
Biotechnology is a perfect way to improve crop production by enhancing its capacity to be resistant to abiotic stress. Abiotic stresses have a detrimental effect on crop plants which contribute to plant efficiency and productivity declines. All of the abiotic stresses induce an enhanced development of reactive oxygen species (ROS). Specific abiotic stresses hinder the growth of plants by various pathways but both because ROS rates rise and conflict with homeostasis of ROS. Melatonin can improve the economy by improving crop production and raising the possibility of abiotic stress management. It shows the different roles of melatonin in a plant system, which can be helpful in enhancing environmentally friendly crop development and maintaining nutritional security that can impact social life. Another crucially significant factor is the development of melatonin-rich food crops such as rice, fruits and vegetables by mixing conventional and modern breeding approaches. This method is an improvement in plant tolerance to biotic and abiotic stress that can lead to improved crop yields, and the nutritional added benefit of foods for solving food safety problems.